1965
DOI: 10.1111/j.1151-2916.1965.tb14794.x
|View full text |Cite
|
Sign up to set email alerts
|

Defect Structure and Electrical Conductivity of ThO2-Y2O3 Solid Solutions

Abstract: Compositions in the system Th02-Y01 6 were coprecipitated as oxalates and converted to oxides. Disks were pressed and sintered in oxygen at 1400" to 2200°C. Densities of the sintered disks were 96 to 98% of theoretical. Solid solutions with the fluorite-type structure were formed up to 20 to 25 mole yo YOl,s at 1400OC and up to 45 to 50 mole ' % Y O 1 .~ at 2200°C. Density data showed that these solid solutions correspond to Thl-,Y,Oz-o.s,, having a complete cation sublattice filled by T h 4 + and Y3+ ions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…Such materials produce one oxygen vacancy per added impurity atom due to the charge neutrality condition. It has been reported that the variation of lattice parameter with composition can be accounted for by the relative size of the ions [26]. In case of compound like Pu(C,O), when carbon atom is replaced by oxygen atom of smaller size, the lattice parameter of Pu(C,O) has been found decreasing [27].…”
Section: Dilatometrymentioning
confidence: 98%
“…Such materials produce one oxygen vacancy per added impurity atom due to the charge neutrality condition. It has been reported that the variation of lattice parameter with composition can be accounted for by the relative size of the ions [26]. In case of compound like Pu(C,O), when carbon atom is replaced by oxygen atom of smaller size, the lattice parameter of Pu(C,O) has been found decreasing [27].…”
Section: Dilatometrymentioning
confidence: 98%
“…Due to radioactivity and costs, thoria or hafnia-based electrolytes are rather rarely applied in steel industry [104,105].…”
Section: Cazro 3 -Based Electrolytes For Oxygen Electrochemical Probesmentioning
confidence: 99%
“…Also from a more fundamental point of view, the Th 1Àx RE x O 2Àx/2 systems are intriguing because a large amount of defects in the form of oxygen vacancies are formed to compensate for the substitution of Th 4+ cations by RE 3+ cations, especially at high REE concentrations [16]. In a different context, ThO 2 doped with REOs are also studied because of the high anion (O 2À ) conductivity of these materials induced by the presence of oxygen vacancies [17][18][19]. Therefore, these materials could be used as solid electrolytes in e.g.…”
Section: Introductionmentioning
confidence: 98%